2020
DOI: 10.18291/njwls.v10i1.118679
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Hindrances to the Retention of Older Healthcare Workers

Abstract: The Swedish healthcare sector is currently experiencing recruitment difficulties combined with increasing demand for healthcare services. This study accordingly seeks knowledge of the obstacles to and opportunities for retaining older employees in the Swedish healthcare sector. Results of interviews with line managers and human resource (HR) partners indicate that the informants have positive attitudes toward older healthcare workers in general, particularly acknowledging their contributions based on long expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 48 publications
0
15
0
1
Order By: Relevance
“…Traditionally these distinct elites have been seen as largely separate, characterized by differing cultures and minimal social integration between the two' (Edling et al, 2015). A study of the elite in CSOs (Jonsson & Lagerlöf Nilsson, 2007) shows that this group is more open than most other elite groups when it comes to socio-cultural composition, although it still seems to be characterized by a strong representation of individuals with higher education and by a low representation of women in top positions. That study also showed that direct influence and exchange of information with other fields only pertains to a small group of leaders.…”
Section: Homogeneity Attributes and Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally these distinct elites have been seen as largely separate, characterized by differing cultures and minimal social integration between the two' (Edling et al, 2015). A study of the elite in CSOs (Jonsson & Lagerlöf Nilsson, 2007) shows that this group is more open than most other elite groups when it comes to socio-cultural composition, although it still seems to be characterized by a strong representation of individuals with higher education and by a low representation of women in top positions. That study also showed that direct influence and exchange of information with other fields only pertains to a small group of leaders.…”
Section: Homogeneity Attributes and Resourcesmentioning
confidence: 99%
“…That study also showed that direct influence and exchange of information with other fields only pertains to a small group of leaders. These are in most cases men who have leading positions not only in civil society, but also within politics, and more seldom in science, culture, and administration (Jonsson & Lagerlöf Nilsson, 2007).…”
Section: Homogeneity Attributes and Resourcesmentioning
confidence: 99%
“…Indicated associations with preferences to continue working in older ages were seen where there existed improved resources to boost capability for freedom of choice in terms of participation and influence over decisions, as well as improved learning and competence development. In a study, Jonsson and colleagues (2021) identified the opportunities to make individual deals that match one's competence and experience as the most important for public-sector employees' retirement preferences (Jonsson et al, 2020).…”
Section: Conversion Factors -The Crafting Of Resources At Work For Capability Across Systemsmentioning
confidence: 99%
“…Mindezt az elmúlt két évben zajló globális koronavírus-járvány is megerősítette. A munkaerőhiány problémája azonban -párhuzamosan az elöregedő társadalmakra jellemző egészségügyi szolgáltatások iránti kereslet növekedésével -évtizedes távlatban erőteljesen jelen van a szektorban, nem csak Magyarországon, hanem Európában, illetve a világ többi részén is (Glinos, 2014;Jonsson et al, 2020;Lorkowski és Jugowicz, 2020). A hazai helyzetet jól szemlélteti, hogy 2021 decemberében az Országos Kórházi Főigazgatóság (2022) országosan 578 tartósan betöltetlen háziorvosi körzetről adott jelentést, amelyek jelentős része már több, mint 12 hónapja, de nem elenyésző részük akár 10-15 éve is ebben a státuszban vannak.…”
Section: Bevezetésunclassified